Case report of a stuck hemodialysis central venous catheter: from endovascular intervention to median sternotomy - Reza Eka Putra; Prasetyo Edi; Andreas Andri Lensoen (Indonesian Vascular Access Association (IVAA), 2023)
Background: Extended uses of hemodialysis catheters is often associated with thrombosis and fibrosis of the central vein around the catheter. The removal becomes complex when the catheter is stuck in a central vein. This case report presented a complex stage of removing a stuck catheter in the central vein. Case Report: A 45-year-old man complained of a stuck hemodialysis catheter in the left subclavian vein, which had been placed 8 months previously. An endovascular intervention has been tried using traction and snaring of the catheter tip, but it cannot be removed because the body part of the catheter is firmly attached to the central vein, so we decided to evacuate the catheter using the median sternotomy procedure. We found an adhesion between the left innominate vein's wall and the catheter's body about 4 cm from the catheter tip. The left innominate vein was incised longitudinally while detaching the catheter against the vein. We repair the left Innominate vein without using a graft. Conclusion: A stuck catheter to the central vein was an unexpected complication due to the removal of the hemodialysis catheter. There are several options for removing a stuck catheter, such as various endovascular interventions and open surgical techniques.